Effects of extreme meteorological conditions in 2018 on European methane emissions estimated using atmospheric inversions. (24th January 2022) - Thompson, R. L.; Groot Zwaaftink, C. D.; Brunner, D.; Tsuruta, A.; Aalto, T.; Raivonen, M.; Crippa, M.; Solazzo, E.; Guizzardi, D.; Regnier, P.; Maisonnier, M.
Abstract : The effect of the 2018 extreme meteorological conditions in Europe on methane (CH4 ) emissions is examined using estimates from four atmospheric inversions calculated for the period 2005–2018. For most of Europe, we find no anomaly in 2018 compared to the 2005–2018 mean. However, we find a positive anomaly for the Netherlands in April, which coincided with positive temperature and soil moisture anomalies suggesting an increase in biogenic sources. We also find a negative anomaly for the Netherlands for September–October, which coincided with a negative anomaly in soil moisture, suggesting a decrease in soil sources. In addition, we find a positive anomaly for Serbia in spring, summer and autumn, which coincided with increases in temperature and soil moisture, again suggestive of changes in biogenic sources, and the annual emission for 2018 was 33 ± 38% higher than the 2005–2017 mean. These results indicate that CH4 emissions from areas where the natural source is thought to be relatively small can still vary due to meteorological conditions. At the European scale though, the degree of variability over 2005–2018 was small, and there was negligible impact on the annual CH4 emissions in 2018 despite the extreme meteorological conditions. This article is part of a discussion meeting issue 'Rising methane: is warming feeding warming? (part 2)'.